2012
DOI: 10.1126/scitranslmed.3004291
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Sleep-Wake Cycle and Diurnal Fluctuation of β-Amyloid in Mice with Alzheimer’s Disease Pathology

Abstract: Aggregation of amyloid-β (Aβ) in the brain begins to occur years prior to the clinical onset of Alzheimer’s disease (AD). Prior to Aβ aggregation, levels of extracellular, soluble interstitial fluid (ISF) Aβ, which are regulated by neuronal activity and the sleep-wake cycle, correlate with the amount of Aβ deposition in the brain seen later. The amount and quality of sleep declines with aging and to a greater extent in AD. How sleep quality amount as well as the diurnal fluctuation in Aβ change with age and Aβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
453
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 503 publications
(491 citation statements)
references
References 45 publications
34
453
1
3
Order By: Relevance
“…The sleep-wake changes described in APP-PS1 mice may be due to induced changes in synaptic activity and excitability occurring in brain regions affected by amyloid deposition. 37 In humans, a recent study found that individuals diagnosed with AD had fewer neurons than controls in the intermediate nucleus, a brain region that is thought to promote sleep by inhibiting wake-promoting brain regions. 38 Additionally, the impairment in sleep-dependent declarative memory consolidation observed in subjects with high amyloid load was found to be mediated by the loss in frontal SWA, 39 suggesting that changes in SWS lie downstream of Aβ42 deposition.…”
Section: Discussionmentioning
confidence: 99%
“…The sleep-wake changes described in APP-PS1 mice may be due to induced changes in synaptic activity and excitability occurring in brain regions affected by amyloid deposition. 37 In humans, a recent study found that individuals diagnosed with AD had fewer neurons than controls in the intermediate nucleus, a brain region that is thought to promote sleep by inhibiting wake-promoting brain regions. 38 Additionally, the impairment in sleep-dependent declarative memory consolidation observed in subjects with high amyloid load was found to be mediated by the loss in frontal SWA, 39 suggesting that changes in SWS lie downstream of Aβ42 deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Polysomnographic sleep-wake cycle analysis of mice was performed as described previously (Bero et al 2011;Roh et al 2012). Briefly, EEG and electromyogram (EMG) electrodes were implanted simultaneously 10 d prior to recording.…”
Section: Sleep Physiologymentioning
confidence: 99%
“…Although a role for the sleep-wake cycle in the pathogenesis of AD has been proposed previously [26,33,45,54] , this idea has received relatively little attention; however, it has become increasingly compelling in light of recent findings in human molecular and neuroimaging studies. Here we draw together several lines of previous work [1, 2, 8, 10, 12-14, 21, 33, 35-37, 39, 42, 43, 55-67] to outline a hypnic hypothesis of AD pathophysiology.…”
Section: A 'Hypnic Hypothesis' Of Admentioning
confidence: 99%
“…Manipulation of synaptic vesicle release affects β-amyloid levels in interstitial fluid, suggesting a direct mechanistic link [45] . Conversely, both the diurnal fluctuation of CSF β-amyloid levels and the sleep-wake cycle can be normalised by immunisation against β-amyloid-42 in transgenic mouse models of AD [33] . Melatonin has anti-fibrillary actions [31] and inhibits deposition of β-amyloid and development of cognitive deficits in mouse models of AD [23,27,28] .…”
Section: Evidence For the Hypothesis: Cellular And Molecular Links Bementioning
confidence: 99%
See 1 more Smart Citation